Skrining dan Identifikasi Fungi Rhizosfer Indigenous Hutan Buttu Puang sebagai Penghasil Fitohormon Auksin Indole-3-Acetic Acid - Alang, Hasria; Fitri, Fitri; Pasmawati, Pasmawati (Biocaster : Jurnal Kajian Biologi, 2026)
The low amount of IAA production by plants causes plants to often obtain IAA from bacteria that live around the roots or rhizosphere. Exploration of IAA bacteria from Buttu Puang, a protected forest area in West Sulawesi, has never been done. One of the typical plants that inhabit Buttu Puang is the dengen plant (Dillenia serrata). The purpose of this study was to screen and identify the ability of rhizosphere fungi from dengen plants in the Buttu Puang protected forest area to produce IAA. The implication of the study is that isolates with the highest activity can be developed as PGRs producing the phytohormone IAA in the future. The research method began by isolating fungi from the rhizosphere soil. Next, the ability to produce IAA was tested by adding the IAA precursor (tryptophan) to the growth medium. After that, the supernatant was then added with Salkowski. A positive test was indicated by the formation of a pink color at the end of incubation. The results of the study showed that 13 isolates of rhizosphere fungi were found from dengen plants in Buttu Puang Forest, namely isolates DG 1.1, DG 1.2, DG 1.3, DG 1.4, DG 2.1, DG 2.2, DG 2.3, DG 2.4, DG 2.5, DG 3.1, DG 3.2, DG 3.3 and DG 3.4. Qualitative and quantitative tests using Salkowski reagent and spectrophotometer measurements at a wavelength of 530 nm showed that only two isolates were able to produce IAA, namely isolate DG 2.1 (104.09 ppm), and isolate DG 2.5 (39.26 ppm). These results indicate significant differences in physiological potential among isolates, which are thought to be related to the physiological characteristics and IAA biosynthesis pathways of each genus. Macroscopic and microscopic identification showed that isolate DG 2.1 was suspected to be a member of the genus Penicillum, while isolate DG 2.5 was suspected to be an Aspergillus. These findings confirm that the phytohormone-producing rhizosphere microorganisms from dengen plants in Buttu Puang Forest have the potential to be developed as plant growth regulators (PGRs) in the future.